Pricing in the pharmaceutical industry - Kolassa, E. Mick (Henry Stewart Talks, 2009)
Understanding how prices are currently set in the global pharmaceutical industry, The importance of developing a pricing strategy, as opposed to simply setting a price, The factors that must be considered when taking pricing actions, The implications of poor pricing decisions